Differences in Euro-Area Household Finances and their Relevance for Monetary-Policy Transmission - Thomas Hintermaier; Winfried Koeniger (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper quantifies the extent of heterogeneity in consumption responses to changes in real interest rates and house prices in the four largest economies in the euro area: France, Germany, Italy, and Spain. We first calibrate a life-cycle incomplete-markets model with a liquid financial asset and illiquid housing to match the large heterogeneity of households asset portfolios, observed in the Household Finance and Consumption Survey (HFCS) for these countries. We then show that the heterogeneity in household finances implies that responses of consumption to changes in the real interest rate and in house prices differ substantially across the analyzed countries, and across age groups within these countries. The different consumption responses quantified in this paper point towards important heterogeneity in monetary-policy transmission within the euro area.
Keywords: D14; D15; D31; E21; E43; G11; 330; European household portfolios; consumption; monetary policy transmission; international comparative finance; housing